Effect of Shashtika Shali Pinda Sweda & other Ayurvedic Intervention in Cerebral palsy: A Case Report (AYUSHDHARA, 2023)
Cerebral palsy is a disorder that affects muscle tone, movement and motor skills (the ability to move in a coordinated and purposeful way). Cerebral Palsy cannot be correlated with any single disease or condition mentioned in Ayurveda, as it is a multi-factorial disease. The classical signs and symptoms of CP will fit into criteria of Vata Vyadhi spectrum (Vata predominant disease) like Ekangvata, Sarvangvata, Pakshaghata, Pangu, Kampavata etc and Phakkaroga. Although cerebral palsy cannot be completely cured but treatment will generally enhance a child’s abilities. Agnimandya, Amavastha and Kaphavastha should be considered while planning the line of treatment in CP cases. The selected Ayurvedic treatment modality is highly effective in relieving the signs and symptoms and thus reducing the disability in children with CP. Swedana (sudation) is the therapy that relieves the Stambha (stiffness) of the body, mitigate feeling of Guruta (heaviness) and Sheeta (feeling of cold). Shastika shali panda sweda comes under the category of Saagniseda with Snigda dravya as milk and Shalidhanya. It has Snigdha, Guru, Sthira, Sheeta, Tridoshaghna and Brimhanaguna. In this article, an attempt to treat a child with spastic diplegia using multiple Ayurveda treatment modalities. At the end of one year of treatment, Panchkarma procedures along with internal medication resulted in 15-20% improvement in the overall effect of therapy.